ORGANIZATIONAL STRUCTURE OF PUBLIC ADMINISTRATION FOR DEVELOPMENT OF PUBLIC-PRIVATE PARTNERSHIP IN THE AREA OF HOUSING IN UKRAINE: PROBLEMS AND PERSPECTIVES - Korbecjkyj , Myroslav (Theory and Practice of Public Administration, 2020)
Successful implementation of public-private partnership projects in the field of housing in the Ukraine requires the development of a strong organizational (institutional) structure of the public administration itself in the development of partnerships between the public and private sectors. It should be noted that in recent years, despite certain unresolved problems, the legal and regulatory framework for PPPs in Ukraine has been developing towards creating more effective mechanisms for appropriate cooperation between the state, local communities and businesses. The process of positive changes has not passed over the institutional infrastructure for state regulation of PPPs. At the same time, the organizational structure of PPP development governance still lacks clarity of roles and responsibilities of the main institutions involved in PPP development. Ukrainian and foreign specialists such as N. Beletskaya, M. Darcy, M. Dunn, J. -H. Kim, I. Zapatrina, A. Zverev, A. Rodina, Y. Samayeva, A. Shevchenko and many others, have devoted much attention to the problem of PPP mechanism development in Ukraine. At the same time, the domestic professional literature pays very little attention to the problems of development of organizational structure of governance the state and business partnership in Ukraine, and even more so in the area of housing. The task of this work is to characterize the current state of the organizational structure of public administration of public-private partnership development in Ukraine, including in the sphere of housing. The article describes the current state of functioning of the organizational structure of public-private partnership development governance in Ukraine. It assesses the institutional capacity of the Investments department of the Ministry for Development of Economy, Trade and Agriculture of Ukraine, which provides the formation and implementation of public policy in the field of public-private partnership. The current state of consolidation and coordination of the main elements of the institutional infrastructure of public administration for PPP development is analyzed. In particular, it is noted that the system of coordination and registration of PPP projects is fragmented, there is no unified approach to communications between different authorities, low human resources capacity of relevant institutions, and the system of professional education and retraining of public servants with the necessary competences for this activity. It was concluded that today the institutional structure of state support for public-private partnership development in Ukraine has already been formed. It is a positive moment that the key functions of the state on expertise and state regulation of PPPs in Ukraine are now concentrated at the level of one authority - the Ministry for Development of Economy, while PPP projects themselves can be initiated, approved and implemented at the national, regional and local levels by public authorities and local self-government. However, despite the fact that the legal and regulatory framework has been significantly updated over the past few years, the organizational structure of the management of state and business partnership development in Ukraine is still characterized by an unclear distribution of powers between public authorities on the coordination and implementation of such projects, inefficient inter-agency coordination in the formation and implementation of public policy in the field of PPPs, as well as low staff capacity of public authorities. The fact that not a single PPP project in the sphere of housing has been launched to this moment demonstrates the weak institutional capacity of the whole system of public administration for development of state and business partnership in Ukraine, which requires further improvement. In particular, the obvious way out of this situation is the need to create a specialized body with adequate organizational and personnel support, which will be able to perform functions on not only the development, assessment and support of PPP projects, but also act as a subject of legislative initiatives in this area of public policy.